Using content and comparative analysis to contextualize the criteria for urban resiliency planning from international and US cities perspectives - Applegate, Joshua D.; Tilt, Jenna H. (Frontiers in Environmental Science, 2023)
This study focuses on the nuances of urban resiliency how those terms are utilized and operationalized across the global urban realm at varying spatial scale. The European Union and United Nations established international goals, targets, and the specific measurable indicators with both the European Green Deal and their 2030 Sustainable Development Goals (SDGs) to address climate change, with overarching goals of becoming the world’s first carbon neutral continent. Much of this work to “green" cities falls under the concepts of urban resiliency, Green Infrastructure (GI), and ecosystem services (ES). This study seeks to understand the criteria considered for planning, development, implementation and maintenance urban resiliency at city and international levels. By contextualizing and clarifying broad terms like resiliency, ecosystem services, and Green Infrastructure for planners, politicians, and people within communities, our comparative analysis provides detailed understanding of the similarities and differences between plans from a city-to-state perspective, along with analysis of city-to-city comparisons. The objective of this research aims to highlight any variance in types of resiliency planning being done at different scales, including gaps that may exist between US cities and European resiliency strategies for the coming decades. Our results suggest there are differences in focus regarding key aspects of resiliency, as well as the strategies suggested for resilient cities. Differences like importance placed on transportation, future role of Green Infrastructure within urban resiliency planning, and definitional differences regarding ecosystem services. These differences may have potential impacts on outcomes for resiliency project development and maintenance. Keywords: , Green Infrastructure (GI), Sustainable Development Goals (SDGs), urban resiliency